Confirming the links between socio-economic variables and digitalization worldwide: the unsettled debate on digital divide. Issue 3 (4th May 2020) - Mubarak, Farooq; Suomi, Reima; Kantola, Satu-Päivi
Abstract : Purpose: This study aims to statistically verify the links of income and education with information and communication technology (ICT) diffusion across 191 countries of the world taking into account a total of 9 indicators best representing the socio-economic variables. Design/methodology/approach: Multivariate regression analysis was used as a prime method to rigorously test the relationships of income and education with ICT diffusion across 191 countries. Statistical Package for the Social Sciences (V. 22) was used to analyze and predict patterns in the data. Findings: The results support the hypotheses that income and education are positively related to ICT diffusion. The findings statistically confirm that poverty is a leading cause of digital divide worldwide. Research limitations/implications: Academic, policy and practice groups should work in collaboration to fight against digital divide. Present results also imply that digital divide shall never end but rather it can be controlled to an extent with multiple collaborative efforts. Originality/value: Prior research assignments on the digital divide concentrate on exploring the links between few socio-economic and ICT variables in select few regions theoretically. The present work addresses this literature gap by developing and testing two hypotheses to statistically investigate the relationships between a broad set of socio-economic and ICT indicators.